Design and Construction of a 3-Phase Axial Type BLDC Generator for Wind Power Generator - Hadi, Widyono; Rahardi, Gamma Aditya; Fathoni, Ahmad Nur; Pratama, Muhammad Rizal; Firdausi, Hasanur Mohammad (Faculty of Engineering, Universitas Tanjungpura, 2024)
The need for electrical energy in remote areas to improve community welfare must be a concern for universities. The government's ability to build new electricity sources is very minimal because it requires large infrastructure and costs, but the government continues to strive to develop new power plants. Therefore, it is necessary to strive for innovation to build power plants from renewable energy sources. There is a need to use renewable energy as an alternative to replace electrical energy which is increasingly in crisis. One alternative energy that is easy to make is energy that uses magnetic force as a model for generating electricity. Brushless Direct Current (BLDC) motors are an alternative to current DC motors. This three-phase permanent magnet axial flux generator is specially designed for vertical-type wind turbines. This generator consists of two stators and one rotor. where each stator consists of 9 coils and the magnet used is a neodymium permanent magnet. Based on test results, this generator can produce a voltage of 12.57 VDC with a wind speed of 6.84 m/s. So, it can turn on DC lights and charge DC batteries. This three-phase axial BLDC generator was tested in 3 stages, namely without load, using battery load, and DC-light load with wind conditions depending on natural conditions.